Anciens entrepôts urbains de Bruxelles : architecture et construction - Marianne De Fossé (Brussels Studies)
Historical urban warehouses are remarkable structures. Today, however, and despite their robust architecture, they have become vulnerable urban heritage threatened with demolition. Current research being carried out at the Vrije Universiteit Brussel focuses on the development of knowledge about the architecture, operation and construction of warehouses in Antwerp, Brussels and Ghent and their integration in the urban fabric, to support their preservation and respectful adaptive reuse. This paper contains the results of in-depth archival and first on-site investigations of nineteenth and twentieth-century warehouses in the historic city centre of Brussels, covering the first industrial zone around the river Senne and the docks. Eighty demolished and still existing urban warehouses are analysed by focusing first on the storage of some well-represented goods: hay, timber, beer and textile. The analysis shows that the four goods correspond to four types of warehouses that differ in their architecture, organisation, construction and integration in the urban fabric.